Use efficiency and responsivity to nitrogen of common bean cultivars - Leal, Fábio Tiraboschi [UNESP]; Filla, Vinícius Augusto [UNESP]; Bettiol, João Victor Trombeta [UNESP]; De Sandrini, Fernando Oliveira Turci [UNESP]; Mingotte, Fábio Luíz Checchio [UNESP]; Lemos, Leandro Borges [UNESP] (FapUNIFESP (SciELO), 2019)
Common beans are the main source of protein in underdeveloped countries, and nitrogen (N) is one of the nutrients the most limits the productivity of this crop. This study, under field conditions, aimed to: A) determinate through efficiency indices how N is used by 16 cultivars of common beans; and b) classify these cultivars regarding use efficiency and responsivity to N application. The experimental design was in randomized blocks in split-plot scheme, with four replicates. Main plots consisted of 16 cultivars of common beans commercially classified as ‘Carioca type’. Subplots comprised two rates of N: 20 and 120 kg ha-1 applied as top-dressing. The evaluations were number of pods per plant and grains per pod, hundred-grain weight, shoots dry matter at full flowering, straw and grains dry matter at physiological maturity and grain yield. Based on the dry matter and its nutrient contents, the N accumulations were calculated in shoots and grains. The agronomic, physiological, agro-physiological, recovery and use efficiencies of N were calculated. Cultivar BRSMG Uai stands out by agronomic, physiological, recovery and use efficiencies of N. Genotypes BRSMG Uai, BRS FC402, IPR Campos Gerais, IPR Maracanã and TAA Bola Cheia are efficient and responsive to top-dressing N application.
Eficiência de uso e responsividade ao nitrogênio de cultivares de feijoeiro comum
Keywords: Dry matter; Genotypes; Grain yield; Nitrogen accumulation; Phaseolus vulgaris L